Approximation of functions from the Sobolev space by algebraic polynomials - Konovalov , V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A theorem that asserts the simultaneous approximation of functions and their derivatives by means of algebraic polynomials is established for the Sobolev spaces ω∞r(Ω).